The Book of Isaiah in Contemporary Research - Hays, Christopher B. (Religion compass, 2011)
This article surveys scholarship on the book of Isaiah since roughly the start of the 21st century. Noting that theories of the book's formation based on internal textual data have not commanded consensus, it calls for stronger methodological controls for models of composition and redaction, on the basis of comparative data from other ancient Near Eastern texts, especially prophetic texts. Although there has been an outpouring of scholarship from every angle, significant recent trends include centripetal/holistic approaches to the book and study of its reception history.